Rural to Urban Migration as A Class Struggle in Selected Tanzanian Young Adult Novels - Peter Madoshi, John; Hamad, Salma O.; Kilatu, Emmanuel (Cultural Arts Research and Development, 2025)
This study examined a theme of rural to urban migration as highlighted in selected Tanzanian young adult novels. Significantly, the study sought to generate some knowledge on class struggle revealed in the selected young adult novels in Tanzanian society. The study has used Marxist social critical theory as a literary criticism. We have examined qualitatively rural to urban migration as a phenomenon occurring in Tanzanian society as depicted in the selected young adult novels. We argued that rural to urban migration, as depicted in selected literary works, is a social indicator of social transformation in which class struggle emerges as a reaction to exploitation, class stratification and poverty caused by change of mode of production. We also observed that such young adult mobility affects the social welfare of the society culturally, socially and economically. drains the rural labour by creating a class of urban cheap labourers who threaten the material and moral prosperity of the society. We, thus, concluded that young adult novels mirror the social transformation in which a change of mode of production causes a class struggle among the young adults.